A Vibration-Related Design Parameter Optimization Method for High-Speed Elevator Horizontal Vibration Reduction - Lemiao Qiu; Zili Wang; Shuyou Zhang; Lichun Zhang; Jie Chen (Shock and Vibration)
High-speed elevator horizontal vibration (HsEHV) is a problem that seriously affects ride comfort. To solve this problem, a design parameter optimization method for HsEHV reduction was studied. A dynamic equation of HsEHV was established, and its response value was calculated using a precise integration method. The influence of the design parameters on horizontal vibration was also analyzed. An optimization model of the design parameters for HsEHV reduction was constructed, and the response surface model of objective function (the peak-to-peak value of horizontal vibration acceleration) was constructed using Latin hypercube sampling. We adopted a multiobjective genetic algorithm to optimize the design parameters for horizontal vibration reduction and used the min-max standardization method to select an optimal solution set. Finally, a KLK2 high-speed elevator made by Canny Elevator Co., Ltd., was utilized as an example to analyze the influencing factors of HsEHV, optimize the design parameters to reduce horizontal vibration, and verify the optimized results using numerical calculation and prototype testing.